Inland populations of sugar maple manifest higher phenological plasticity than coastal populations - Zhou, Yongzhi; Bai, Chunmei; Guo, Xiali; Mohytych, Vasyl; Klisz, Marcin; Delagrange, Sylvain; Rossi, Sergio (Frontiers in Ecology and Evolution, 2023)
Plasticity is vital for plants to rapidly acclimate to environmental changes, especially under the climate change. Global warming could advance bud break and extend the growing season, but it also increases the risk of frost damage to developing leaves. In this study, we explored the phenological plasticity of bud burst of half-sib family sugar maple (Acer saccharum Marsh.) seedlings from 11 seed origins in two common gardens at the center and the northern edge of the species distribution in Quebec, Canada. Results showed that the phenological plasticity of sugar maple originating from inland was significantly higher than those from coastal areas at the beginning of leaf development. This discrepancy may result from the long-term frost change frequency of seed origins. Our study suggests that in the context of climate warming, the higher plasticity observed in sugar maple originating from inland areas may benefit from the phenological adaptation of sugar maple and the survival of local populations. It also suggests that inland populations may have a higher potential regarding to assisted migration, but this needs to be confirmed for other functional traits than phenology.